Scale and technical efficiency of development finance institutions in Malaysia - Ong, Hway-Boon; Selamat, Zaheran; Ismail, Norhazlin; Habibullah, Muzafar Shah (Universiti Utara Malaysia, 2005)
This study focuses on the performance of credit guarantee corporations and development financial institutions that promotes industrialisation,agricultural investment, and growth in small and medium enterprises in Malaysia. A non-parametric technique is used in this analysis to determine the scale and technical efficiency of development financial institutions since the performance of these institutions is directly reflected in the development and economic growth of the sector they promote. The empirical findings we obtained suggested that all development financial institutions are operating satisfactorily in extending their services to small and medium local enterprises.